Influence of growing and doping methods on radiation hardness of n-Si irradiated by fast-pile neutrons - Dolgolenko, A.P.; Litovchenko, P.G.; Litovchenko, A.P.; Varentsov, M.D.; Lastovetsky, V.F.; Gaidar, G.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
Silicon n-type samples with resistivity ~2.5*10³ Ohm*cm grown by the method of a floating-zone in vacuum (FZ), in argon tmosphere (Ar) and received by the method of transmutation doping (NTD) are investigated before and after irradiation by various doses of fastpile neutrons at room temperature. The radiation hardness of n-type silicon is shown to be determined first of all by the introduction rate of defect clusters and their parameters and then by the introduction rate of defects into the conducting n-Si matrix. The presence of oxygen, argon atoms and A-type defects (dislocation loops of the interstitial type) mainly increases the radiation hardness of n-Si. The effective concentration of carriers in irradiated silicon was calculated in the framework of Gossick's model taking into account the recharges of defects both in the conducting matrix of n-Si and in the space-charge regions of defect clusters. Grown by the method of the floating-zone melting in argon atmosphere the neutron-transmutation- doped silicon (NTD) has elevated radiation hardness. The introduction rate of divacancies in the conducting matrix of n-Si (NTD) is about five times less than in n-Si (FZ) and ~2 times less than in n-Si (Ar). The availability of the deformation strain field surrounding the argon-type impurities as well as A-type defects is supposed to promote the annihilation of divacancies with interstitial atoms of silicon.